“Atreverse a pensar es empezar a luchar”: elementos para el análisis de la revista colombiana “Alternativa” - Agudelo Castro, Carlos (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This case study of leftist journalism in Latin America defines the characteristics, in specific historical circumstances, of Alternativa, a magazine published in Colombia from 1974 to 1980. The model was based on four objectives: counter informing; doing investiga-tion, analysis and interpretation; divulging the struggles of the peo-ple; and propitiating the unity of the left. The Marxist background of its founders, which included Nobel Prize winner Gabriel García Márquez, determined the magazine ́s content and neutral approach toward the left parties, while reaching a wide mass-circulation readership. Principled political differences led the magazine to sev-eral crises that fostered its journalistic evolution, probing the limits of press freedom in its struggle to survive against a reckless and corrupt regime. The narrative reviews the history of the country as it was portrayed in the publication, contrasting it with that of the establishment’s media; it highlights paramount issues such as hu-man rights violations, corruption and the role of the press, through the coverage of Colombia’s armed forces and police; and it explores the magazine’s complex relationship with the left, which eventually led to its demise.